Production of single-chain fragment variable (scFv) antibodies specific to plasma membrane epitopes on bull Y-bearing sperm - Wannaluk Thaworn (2020)
© 2020 Taylor & Francis Group, LLC. Distinguishing between bull Y- and X-bearing sperm populations is advantageous for techniques using sexed bull semen. The aim of this study was to produce a single-chain fragment variable (scFv) antibody against plasma membrane epitopes on bull Y-bearing sperm. Variable heavy (VH)- and variable light (VL)-region genes generated from a hybridoma cell secreting a specific Y-bearing sperm monoclonal antibody (mAb-1F9) were cloned and expressed. The expected sizes of the DNA bands were ∼350 bp for the VH gene and ∼318 bp for the VL gene. The VH and VL genes were generated and used to construct an scFv gene (∼650 bp), which was expressed in E.coli TG1 cells and produced the corresponding soluble scFv antibody. Compared with the parent mAb-1F9, the scFv antibodies presented a high affinity for Y-bearing sperm and low cross-reactivity with X-bearing sperm. An immunofluorescence analysis confirmed that the scFv antibodies and mAb-1F9 recognize epitopes on the Y-bearing sperm surface. The fluorescence signal was strong on the plasma membrane of Y-bearing sperm but very weak for X-bearing sperm. This study aids the application and production of engineered scFv antibodies specific to Y-bearing sperm to distinguish between Y- and X-bearing sperm populations for techniques involving sexed bull semen.